Implications Alkaline Phosphatase And Bone Specific Alkaline Phosphatase In Periodontitis. - Mathangi.R, Yaongamphi Vashum, Jayamathi Govindarajan,Nalini Devarajan,Shila.S (Drugs and Cell Therapies in Hematology, 2021)
Alkaline phosphatase is the most preferred enzyme of diagnosis in bone diseases and in the study of osteobiology.Incidentally alkaline phosphatase is the most widely assessedenzyme in clinical medicine.The significance of alkaline phosphatase in diagnosis and prognosis of various skeletal disorders are widely reported.This review specifically aims to understand the role of alkaline phosphatase and its bone specific isoenzyme,BAPin ascertaining alveolar bone loss associated with periodontitis.